Did unemployed workers choose not to work in interwar Britain? Evidence from the voices of unemployed workers - Sohn, Kitae (2013)
This paper revisits the controversy over whether unemployed workers in interwar Britain chose not to work because unemployment benefits were too generous. Economists have generally neglected the actual expressions of unemployed workers on the subject, while focusing rather narrowly on the economic aspects of work. The paper takes seriously the voices of unemployed workers, providing economists with a historian's perspective. Unemployment brought workers isolation, family breakdowns, anxiety-ridden idleness, shame and hardship for spouses. Their testimonies render implausible the argument that they voluntarily elected not to work. The evidence emphasises that work meant more than a source of income: it had positive social aspects. © 2013 © 2013 Taylor & Francis.